Proceedings of the 2013 ACM SIGSAC Conference on Computer &Amp; Communications Security - CCS '13 2013
DOI: 10.1145/2508859.2516674
|View full text |Cite
|
Sign up to set email alerts
|

FPDetective

Abstract: In the modern web, the browser has emerged as the vehicle of choice, which users are to trust, customize, and use, to access a wealth of information and online services. However, recent studies show that the browser can also be used to invisibly fingerprint the user: a practice that may have serious privacy and security implications.In this paper, we report on the design, implementation and deployment of FPDetective, a framework for the detection and analysis of web-based fingerprinters. Instead of relying on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(43 citation statements)
references
References 12 publications
1
39
0
3
Order By: Relevance
“…As new features are included within web browsers to draw images, render 3D scenes or process sounds, new attributes have been discovered to strengthen the fingerprinting process [5], [7], [9], [10], [18], [19], [20]. Additionally, researchers have performed large crawls of the web that confirm a steady growth of browser fingerprinting [1], [2], [9], [22]. While most of these studies focused on desktops, others demonstrated they could successfully fingerprint mobile device browsers [11], [14].…”
Section: Background and Motivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As new features are included within web browsers to draw images, render 3D scenes or process sounds, new attributes have been discovered to strengthen the fingerprinting process [5], [7], [9], [10], [18], [19], [20]. Additionally, researchers have performed large crawls of the web that confirm a steady growth of browser fingerprinting [1], [2], [9], [22]. While most of these studies focused on desktops, others demonstrated they could successfully fingerprint mobile device browsers [11], [14].…”
Section: Background and Motivationsmentioning
confidence: 99%
“…Websites track their users for different reasons, including targeted advertising, content personalization, and security [2]. Traditionally, tracking consists in assigning unique identifiers to cookies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure QoE during web browsing sessions, several tools have been developed by the research community. FPDetective [13] uses a PhantomJS 4 and Chromium based automation insfrastructure, OpenWPM [14] performs automated web browsing driven by Selenium 5 while supporting stateful and stateless measurements and the Chameleon Crawler 6 is a Chromium based crawler used for detecting browser fingerprinting. Fourth Party [15] instruments the Mozilla-Firefox browser and Web Xray [16] is a PhantomJS based tool for measuring HTTP traffic.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The same year, Acar et al performed a much larger crawl by visiting the homepages of top Alexa 1 million websites and 25 links of 100,000 Alexa websites with the FPDetective framework [69]. They made modifications to the rendering engine to intercept and log access to browser and device properties that could be used for fingerprinting.…”
Section: Adoption Of Fingerprinting On the Webmentioning
confidence: 99%